STRONG CONVERGENCE THEOREMS FOR STRICTLY ASYMPTOTICALLY PSEUDOCONTRACTIVE MAPPINGS IN HILBERT SPACES - Saluja, Gurucharan Singh; Nashine, Hemant Kumar (IndoMS, 2010)
We propose a new (CQ) algorithm for strictly asymptotically pseudo-contractive mappings and obtain a strong convergence theorem for this class ofmappings in the framework of Hilbert spaces.DOI :Â http://dx.doi.org/10.22342/jims.16.1.29.25-38